2018
DOI: 10.1515/rrlm-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Administration of valine, leucine, and isoleucine improved plasma cholesterol and mitigated the preatherosclerotic lesions in rats fed with hypercholesterolemic diet

Abstract: Hypercholesterolemia has a major contribution to the occurrence and progression of atherosclerotic lesions. Recent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The potential mechanism of furan-induced hepatocyte apoptosis was discussed based on the metabolites and pathways (Table and Figure C–F). Previous research has displayed that valine, leucine, and isoleucine can improve the cholesterol level, 7α-Hydroxy-3-oxo-4-cholestenoate is related to the initiation of the synthesis, and cholic acid is conjugated with taurine or glycine before secretion. In addition, bilirubin, fluvastatin, and bile salts are included in the pathway of bile secretion, and this pathway is associated with primary bile acid biosynthesis and the tight junction.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism of furan-induced hepatocyte apoptosis was discussed based on the metabolites and pathways (Table and Figure C–F). Previous research has displayed that valine, leucine, and isoleucine can improve the cholesterol level, 7α-Hydroxy-3-oxo-4-cholestenoate is related to the initiation of the synthesis, and cholic acid is conjugated with taurine or glycine before secretion. In addition, bilirubin, fluvastatin, and bile salts are included in the pathway of bile secretion, and this pathway is associated with primary bile acid biosynthesis and the tight junction.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in 2018, we assessed the role of valine, leucine and isoleucine on the occurrence and progression of atherosclerosis in rats receiving hypercholesterolic diet. The comparative study of the three essential amino acids revealed that valine induced a faster response than leucine and isoleucine on the improvement of biochemical parameters, but no significant differences between the three amino acids in terms of their protective ability, according to the histopathological lesion assessment [ 26 ]. Still, further studies in order to assess the precise molecular mechanism by which these amino acids influence the triglyceride levels are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In its turn, it is known that L-glutamine with L-alanine or as a dipeptide is able to induce cytoprotective effects mediated by heat shock protein 70 (HSP70)-associated responses to muscle damage and inflammation [ 37 ]. Isoleucine is known for its protective ability having a beneficial contribution to the vascular wall [ 38 ]. Carnosine possesses a broad range of protective properties, including hypoglycemic, anti-inflammatory, and anti-oxidative effects [ 39 ].…”
Section: Discussionmentioning
confidence: 99%